Why are women still leaving academic medicine? A qualitative study within a London Medical School - Christopher J Peters; Lesley Regan; Victoria Salem; Clare Lloyd; Dhruti Hirani (BMJ Open)
Objectives To identify factors that influenced women who chose to leave academic medicine.Design and main outcome measures Independent consultants led a focus group of women in medicine who had left academia after completion of their postgraduate research degree at Imperial College London Faculty of Medicine. Thematic analysis was performed on the transcribed conversations.Participants and setting Nine women physicians who completed a postgraduate degree (MD or PhD) at a large London Medical School and Academic Health Sciences Centre, Imperial College London, but did not go on to pursue a career in academic medicine.Results Influences to leave clinical academia were summarised under eight themes—career intentions, supervisor support, institutional human resources support, inclusivity, work–life balance, expectations, mentors and role models, and pregnancy and maternity leave.Conclusion The women in our focus group reported several factors contributing to their decision to leave clinical academia, which included lack of mentoring tailored to specific needs, low levels of acceptance for flexible working to help meet parental responsibilities and perceived explicit gender biases. We summarise the multiple targeted strategies that Imperial College London has implemented to promote retention of women in academic medicine, although more research needs to be done to ascertain the most effective interventions.